Misophonia and comorbid psychiatric symptoms: a preliminary study of clinical findings - Erfanian, M; Kartsonaki, C; Keshavarz, A (Taylor and Francis, 2019)
OBJECTIVE:Misophonia is a neurophysiological disorder, phenotypically characterized by heightened autonomic nervous system arousal which is accompanied by a high magnitude of emotional reactivity to repetitive and pattern-based auditory stimuli. This study identifies the prevalence of psychiatric symptoms in misophonia sufferers, the association between severity of misophonia and psychiatric symptoms, and the association between misophonia severity and gender. METHODS:Fifty-two misophonia sufferers, 30 females (mean age= 40.93 ± 15.29) and 22 males (mean age= 51.18 ± 15.91) were recruited in our study and they were diagnosed according the criteria proposed by Schröder et al The participants were evaluated by the A-MISO-S for the severity of misophonia and the MINI to assess the presence of psychiatric symptoms. RESULTS:The most common comorbid symptoms reported by the misophonia patients were respectively PTSD (N = 8, 15.38%), OCD (N = 6, 11.53%), MDD (N = 5, 9.61%), and anorexia (N = 5, 9.61%). Misophonia severity was associated with the symptoms of MDD, OCD, and PTSD as well as anorexia. There was an indication of a significant difference between men and women in the severity of misophonic symptoms. CONCLUSION:Our findings highlight the importance of recognizing psychiatric comorbidity among misophonia sufferers. The presence of these varying psychiatric disorders' features in individuals with misophonia suggests that while misophonia has unique clinical characteristics with an underlying neurophysiological mechanism, may be associated with psychiatric symptoms. Therefore, when assessing individuals with misophonia symptoms, it is important to screen for psychiatric symptoms. This will assist researchers and clinicians to better understand the nature of the symptoms and how they may be interacting and ultimately allocating the most effective therapeutic strategies.